2015
DOI: 10.1002/chem.201406416
|View full text |Cite
|
Sign up to set email alerts
|

Multifold Fluorescence Enhancement in Nanoscopic Fluorophore–Clay Hybrids in Transparent Aqueous Media

Abstract: Valuable emissive properties of organic fluorophores have become indispensable analytical tools in biophotonics, but frequently suffer from low solubilities and radiationless deactivation in aqueous media, that is, in biological ambience as well. In this report, nanoscaled dye-clay hybrids based on laponite, Na0.7 {(Li0.3 Mg5.5 )[Si8 O20 (OH)4 ]}, are taken advantage of to solubilize neutral dyes, which are natively not encountered in water. Previously reported efficiency and solubility bottlenecks of such hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 46 publications
(25 reference statements)
3
19
0
Order By: Relevance
“…For fluorescence microscopy analyses, laponite was loaded with rhodamine B according to a previously published procedure . The rhodamine B-modified laponite was immobilized by MIMIC as described before.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For fluorescence microscopy analyses, laponite was loaded with rhodamine B according to a previously published procedure . The rhodamine B-modified laponite was immobilized by MIMIC as described before.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, laponite particles were loaded with Nile Red, which typically forms H-dimers on such surfaces, strongly diminishing the fluorescence quantum yield of the dye. However, upon incubation with choline, the interaction of Nile Red dimers on the laponite surface is weakened, and the H-dimers dissociate to a certain extent . In this way, a response of the surface indicating the presence of choline is generated, which is observable with fluorescence microscopy or spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the interlayer cations (such as sodium) balance the negative charges of the sheet (see Scheme ). Smectites, which belong to this group, are known for their ion-exchange properties with applications in many fields such as water depollution, catalysis, or drug delivery systems The interlayer compensation cations can be replaced by a wide range of cations, either mineral or organic, such as organic cationic dyes. ,− In this case, the interactions of the clay mineral surface with the molecules of the dyes can modify their photochemistry and optical properties. , Recently, we have shown that phyllosilicates can be used to control the photophysics of the triarylmethane dye crystal violet . The interaction of the cationic dye, attracted by the negative octahedral charge of a commercially available synthetic 2:1 phyllosilicate (Laponite), with the platelet surface turns the nonemissive dye into a fluorescent compound .…”
Section: Introductionmentioning
confidence: 99%